2018
DOI: 10.1159/000488112
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrence in Low-Risk Endometrial Cancer: A Case-Control Study

Abstract: Aim: The aim of this study was to investigate the risk factors for recurrence in patients with low-risk endometrial cancer (EC). Patients and Methods: This retrospective study was performed using 10 gynecological oncology department databases. Patients who met the following criteria were included in the study: (a) endometrioid-type histology, (b) histological grade 1 or 2, (c) no or < 50% myometrial invasion, (d) no intraoperative evidence of extrauterine spread, and (e) the patient underwent at least a pelvic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…LVSI is another well-documented prognostic factor in endometrial cancer. Patients with LVSI have 5.8 times the increased risk of recurrence ( 34 ). Guntupalli et al ( 13 ) showed that LVSI had a 95% negative predictive value for nodal disease.…”
Section: Discussionmentioning
confidence: 99%
“…LVSI is another well-documented prognostic factor in endometrial cancer. Patients with LVSI have 5.8 times the increased risk of recurrence ( 34 ). Guntupalli et al ( 13 ) showed that LVSI had a 95% negative predictive value for nodal disease.…”
Section: Discussionmentioning
confidence: 99%
“…In current study, 58 patients (50%) had accompanying metabolic disease so significant percent of our patients were not having excellent health status. Unfortunately, adjuvant treatment of the endometrial cancer is not powered by the phase studies, therefore decision was made case by case 12 . In our study, there is very low rate of systemic relapse and one patient died during platin based adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic factors, including the patients' clinical characteristics, surgical procedures, pathological features, adjuvant treatments, genetic alterations, and hematological parameters, which are predictors for cancer-related inflammation, have been studied in many EC reports [14][15][16][17][18][19][20][21]. Nevertheless, most of the analyses included heterogeneous groups of patients whose diseases had different stages or risk groups.…”
Section: Introductionmentioning
confidence: 99%